Amyand’s hernia in children: A 20-year experience at a tertiary referral hospital - Tartar, Tugay; Saraç, Mehmet; Bakal, Unal; Akdeniz, İbrahim; Kazez, Ahmet (My University, 2022)
Aim: Amyand’s hernia is detected in 0.42%–1% of children with inguinal hernia (IH) and is quite difficult to diagnose prior to surgery. \rThere is no consensus on its treatment.\rMaterials and Methods: The records of patients who underwent IH repair and were diagnosed with Amyand’s hernia between 2001 \rand 2019 were retrospectively analysed in terms of age, gender, complaints at presentation, side of IH, treatment methods (with \rappendectomy or reduction of appendix), complications, duration of hospital stay and follow-up.\rResults: In total, 3,577 patients (male/female: 3,045/532) who underwent surgery for IH and 1,898 patients who underwent \rappendectomy were analysed. Cases with Amyand’s hernia (n=47, male/female: 41/6) accounted for 1.31%, 1.4% and 0.31% of all IH, \rincarcerated/strangulated hernia and appendectomy cases, respectively. The median age was 3 months. In one case, the appendix \rwas located within the left hernial sac. One patient presented with a complaint of recurrent abscess in the right inguinal region. In all \rcases, the diagnosis was made intra-operatively based on identification. In 23.4% of the cases with Amyand’s hernia, appendectomy \rwas performed. In 46 of the 47 cases diagnosed with Amyand’s hernia, inguinal transverse incision and high ligation procedures \rwere performed. Acute appendicitis did not develop during follow-up in cases without appendectomy.\rConclusion: Because the appendix plays an active role in the immune system, especially during childhood, and is used in some \rpathologic cases as luminal supportive tissue, we believe that appendectomy should not be performed if there are no signs of \rinflammation and the appendix can be reducted into the abdomen.
Keywords: Genel ve Dahili Tıp; Cerrahi